2017
DOI: 10.1177/1756285617722706
|View full text |Cite
|
Sign up to set email alerts
|

Alemtuzumab in the long-term treatment of relapsing-remitting multiple sclerosis: an update on the clinical trial evidence and data from the real world

Abstract: Alemtuzumab is a humanized monoclonal antibody approved for the treatment of relapsing-remitting multiple sclerosis (RRMS), given as two annual courses on five consecutive days at baseline and on three consecutive days 12 months later. Here we provide an update on the long-term efficacy and safety of alemtuzumab in RRMS, including real-world experience, and advances in our understanding of its mechanism of action. Recent data from the phase II/III extension study have demonstrated that alemtuzumab reduces rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
90
3
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(98 citation statements)
references
References 71 publications
(88 reference statements)
2
90
3
3
Order By: Relevance
“…The study results have demonstrated that alemtuzumab reduces relapse rates, disability worsening and the rate of brain volume loss over the long term, with many patients achieving no evidence of disease activity. In high proportions of patients, pre‐existing disability remained stable or improved 49. NK cells were reduced to a lesser extent than T and B lymphocytes, with mean counts remaining within the normal range throughout the 2‐year period, which may relate to the much lower expression of CD52 antigen on NK cells compared to T and B lymphocytes.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The study results have demonstrated that alemtuzumab reduces relapse rates, disability worsening and the rate of brain volume loss over the long term, with many patients achieving no evidence of disease activity. In high proportions of patients, pre‐existing disability remained stable or improved 49. NK cells were reduced to a lesser extent than T and B lymphocytes, with mean counts remaining within the normal range throughout the 2‐year period, which may relate to the much lower expression of CD52 antigen on NK cells compared to T and B lymphocytes.…”
Section: Discussionmentioning
confidence: 95%
“…infusion for two treatment courses, 12 mg/day on 5 consecutive days for the first course and 12 mg/day on 3 consecutive days 12 months later for the second course. Retreatment with up to two additional treatment courses, as needed, was recently approved by the EMA based on the data from the long-term extension study [43,49].…”
Section: Introductionmentioning
confidence: 99%
“…These data confirmed how AZB reduces relapse rates, disability worsening, and the rate of brain volume loss over the long term. In a significant proportion of patients, preexisting disability remained stable or improved [38]. Nonetheless the present of safety issues such as infusion related reaction, development of autoimmunity caused by T-cell repopulation occuring through reconstitution of T-cells in the thymus or proliferation of mature cells, infections have been confirmed.…”
Section: Treatment Choices: Future Perspectivesmentioning
confidence: 99%
“…While infusion-associated reactions observed are quite manageable by clinicians, increased risk of infections (e.g: Listeria monocytogenes, herpes virus, cytomegalovirus), and secondary autoimmunity (e.g: idiopathic thrombocytopenic purpura, Graves's disease Goodpasture's syndrome) associated with AZB required a strict and rigorous monitoring even long after last treatment cycle [39]. To do so a clinical surveillance program for AZB has been established; protocol-defined laboratory monitoring including differential blood count, serum creatinine, and urine analysis before administration and monthly thereafter as well physician and patient education have been recommended continuing for 4 years after the last dose of AZB or longer if warranted [38]. This implies a precise patient selection relying on individual diligence and extreme compliance to the monitoring program.…”
Section: Treatment Choices: Future Perspectivesmentioning
confidence: 99%
“…Alemtuzumab has many uses both in haematology as well as other medical specialties. It has been used for a wide variety of conditions including multiple sclerosis,1 aplastic anaemia,2 chronic lymphocytic leukaemia,3 stem cell transplantation,4 lung transplantation,5 renal transplantation6 and vasculitis 7…”
Section: Introductionmentioning
confidence: 99%